The Discovery of Dabigatran Etexilate - van Ryn, Joanne; Goss, Ashley M.; Hauel, Norbert; Wienen, Wolfgang; Priepke, Henning; Nar, Herbert; Clemens, Andreas (Frontiers in Pharmacology, 2013)
Thromboembolic disease is a major cause of mortality and morbidity in the developed world and is caused by an excessive stimulation of coagulation. Thrombin is a key serine protease in the coagulation cascade and numerous efforts have been made to develop safe and effective orally active direct thrombin inhibitors (DTIs). Current anticoagulant therapy includes the use of indirect thrombin inhibitors (e.g. heparins, low-molecular-weight-heparins [LMWHs]) and vitamin K antagonists (VKA) such as warfarin. However there are several caveats in the clinical use of these agents including narrow therapeutic window, parenteral delivery, and food- and drug-drug interactions. Dabigatran is a synthetic, reversible DTI with high affinity and specificity for its target binding both free and clot-bound thrombin, and offers a favorable pharmacokinetic profile. Large randomized clinical trials have demonstrated that dabigatran provides comparable or superior thromboprophylaxis in multiple thromboembolic disease indications compared to standard of care. This minireview will highlight the discovery and development of dabigatran, the first in a class of new oral anticoagulant (NOAC) agents to be licensed worldwide for the prevention of thromboembolism in the setting of orthopedic surgery and stroke prevent in atrial fibrillation.